Stream-dwelling fungal decomposer communities along a gradient of eutrophication unraveled by 454 pyrosequencing - Duarte, Sofia Alexandra Ferreira (2015)
Microbial decomposers, especially a fungal group called aquatic hyphomycetes, play a critical role in processing plant litter in freshwaters by increasing its palatability to invertebrate shredders. Traditionally, communities of aquatic hyphomycetes have been assessed through the identification of spores, which misses non-sporulating taxa. Among new technologies, 454 pyrosequencing stands out as most promising for large-scale species identification. However, very few attempts have been made to validate its effectiveness for assessing the diversity of stream-dwelling fungal communities. We attempted to gain greater insight into the diversity of aquatic fungal communities in streams exposed to various degrees of eutrophication by using the 454 pyrosequencing technology. A total of 173,889 ITS2 pyrosequencing reads with hits for fungi were obtained from the 5 investigated streams. The majority of operational taxonomic units (OTUs) belonged to Ascomycota and the identification to the genus level was achieved for 169 OTUs. Of the total, 135,257 reads (ca. 78%) showed close affinities to aquatic hyphomycete species. Pyrosequencing showed declining fungal diversity in the most eutrophic streams, which was congruent with a reduced diversity found through spore identification. Dominance patterns revealed by connecting representative OTUs to ITS sequences from aquatic hyphomycetes were similar to those determined by traditional spore identification techniques. However, 454 pyrosequencing provided a more comprehensive view of fungal diversity; it captured almost twice as many taxa as spore counts. This study validates the effectiveness of 454 pyrosequencing for surveying the diversity of stream-dwelling fungal decomposer communities. Its application may accelerate the use of these communities for monitoring the integrity of freshwaters.